THE RELATIONSHIP BETWEEN DIETARY PATTERNS AND HEMOGLOBIN LEVELS IN ADOLESCENT FEMALES AT SMKS BINA MANDIRI BONE BOLANGO (Journal of Health, Technology and Science (JHTS), 2025)
Adolescent health efforts are aimed not only at adolescents but also at parents and caregivers to support them in raising healthy adolescents. The purpose of this study is to determine the relationship between dietary patterns and hemoglobin levels in female adolescents at SMK Bina Mandiri Bone Bolango. The approach used in this study is quantitative. This study examines the correlation between dietary patterns and hemoglobin levels in adolescent girls. The results of this study indicate that, based on univariate analysis, the majority of respondents have an ideal nutritional status and adequate intake of energy, protein, and fat. However, many respondents still lack sufficient intake of carbohydrates, vitamin A, and vitamin C, indicating an imbalance in the quality of their daily food intake. The results of the bivariate analysis indicate that only carbohydrate and vitamin C intake are significantly associated with hemoglobin levels. The better the intake of these two nutrients, the higher the respondents' hemoglobin levels tend to be. Meanwhile, other variables such as age, BMI/U, energy, protein, fat, and vitamin A did not show a significant relationship with hemoglobin. This finding suggests that specific macronutrients and vitamin C play a more dominant role in supporting hemoglobin levels in adolescents than other nutritional variables.